Aplikasi Model DMAIC dari Six Sigma dapat Memperbaiki Kualitas Produk Kapur Aktif - Purwo Sudirdjo (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2019)
The need for active lime for the industry is quite a lot, including as a raw material for the production process, management of its main industrial waste and as a filler because many elements of CaO are needed. The needs are still insufficient because the items requested are mostly not in accordance with the specter requested by the user and after all the producers still use traditional methods and their human resources are still low so that meeting consumer demand is very difficult. With the Six Sigma method, the DMAIC model is used to improve and improve the quality of continuous active lime products so as to improve quality and quantity in the hope that consumer needs can be met. Based on the results of testing in the field and making repairs in the production unit to fruition can reduce the value of DPMO in the month before repairs (January - March 2015) amounting to 159506 and in June to 11585 with a percentage decrease of 7.26%. Thus the increase in sigma value in April was 3.43 sigma to 3.77 sigma. if a comparison of rework cost recording is made, the amount of rework cost before repairs is 10.63% of the total production value (Rp. 12,242,000) and after repairs in June 4.63% (Rp. 5,672,000), the savings obtained from the company are 6% (Rp. 7.343689, -) for spending on rework costs. By applying the Six Sigma method the DMAIC model in the production process which always makes continuous improvements can increase profits on the part of producers.